كلمة "الحق" ومعانيها السياقية في القرآن الكريم: دراسة وصفية تحليلية / The word " al Haq " and its contextual meanings in the Qur'an: An analytical descriptive study - Setiyadi, Alif Cahya; Anhar, Anhar; Awaluddin, Ghazali; Marasabessy, Mikael (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
قد انحدر مفهوم الحق في المعاني الحالية عن معناه الحقيقي. كان ادعاء شخص ما عن الحق قد لا يساير ادعاء غيره من الأشخاص أو عكس ذلك. في الواقع قد تم إثبات الحق بكونه نسبيا في حين ومرفوضا في حين آخر. هذه الحالة تؤدي إلى إثبات المعاني المتنوعة التي تثير حيرة الناس في تعيين ما الحق من الباطل. فلذلك تكون العودة إلى معانيها الموجودة في القرآن مهمة للوصول إلى استعمالها استعمالا صحيحا حسب سياقاتها. وتهدف الدراسة إلى جمع معاني الحق واستكشافها والبحث فيها بحثا دقيقا في القرآن الكريم كما ترمي هذه الدراسة إلى إيضاح وجوه العجائب لمعاني الحق التي لا تزيدها التغيرات من وقت لوقت آخر. انتهجت هذه الدراسة المنهج الكيفي بنهج علم الدلالة لاكتساب معاني الحق في مختلف السياقات داخل القرآن الكريم. وقد استعان هذا البحث بالمدونة القرآنية لجمع البيانات والمنهج الوصفي في تحليلها. ونتيجة الدراسة هي: أن معاني الحق في القرآن تحيط بها أمور كثيرة يتصل بعضها ببعض، ومنها: الله وملكوته، بيان الحقيقة، إثبات الحقيقة، الصدق، نصيب وأحكام الشرع، الصواب، والعدل. الكلمات المفتاحية : الحق؛ دلالة سياقية؛ القرآن الكريم Abstrak Nowadays, the concept of absolute truth (al-haq) seems to be blurred. One’s claim that there is an absolute truth on something does not necessary according to the other, and vice versa. In fact, the truth is claimed to be relative, even rejected. Consequently, this condition creates different meanings of the word influencing people decision on what is a thing to be true is and what is not. So, it is fundamental to refer to the Qur'anic meaning of the word (al-haq) to find out the precise use of it contextually. The current study aims at elaborating the meaning of truth (al-haq) according to Al-Qur’an that never change from time to time. The research data are the Qur'anic verses containing the word truth (al-haq) and its derivations. The research mainly relies on the Quranic corpus in collecting the data. It adopted qualitative research with a descriptive approach to find and elaborate the meaning of al-haq in the number of contexts that is occurred in the al-Qur’an. The research found that the term al-haq and its derivations occur 287 times within the corpus. It then, denotes number of meanings including: Allah, proof, credibility, justice, right, true, shariah.